PENGARUH MEDIA VISUAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA KELAS V SDN 166 INPRES BONTORITA - Amelia Naimung Muttalib; Muhajir, Jumiati Nur (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effect of using visual media in Pancasila Education learning on the learning outcomes of fifth-grade students at SDN 166 Inpres Bontorita. Visual media, such as images and infographics, were used as tools to enhance students’ understanding of Pancasila values. This study employed a pre-experimental method with a one-group pretest- posttest design, involving 16 students selected through total sampling. A written test was administered before and after the treatment to measure differences in learning outcomes. The results showed that the average pretest score was 53.75, which increased to 84.375 in the posttest. Inferential analysis using a t-test revealed a t-value of 9.141 > t-table value of 1.753 at a 0.05 significance level, indicating a significant difference between the pretest and posttest results. These findings support the notion that visual media can enhance learning effectiveness, clarify abstract concepts, and foster student motivation and active participation. Visual media also help students connect Pancasila values to real-life contexts, making the learning experience more meaningful. The study recommends the use of visual media as a relevant approach in teaching national values, particularly at the elementary school level.